Study the Impact of Information Technology on The Outputs of The Educational Process by Faculty Members at The University of Jeddah - Darraj, Amnah Ali Ahmed; Al Sulaimani, Taghreed Siddiq (Journal of Educational and Psychological Sciences, 2020)
The aim of this study is to investigate the impact of information and communication technologies on the educational process at the University of Jeddah from the point of view of the faculty members as they are the most influential in the application of information technology within the university. The researcher used the analytical descriptive method through the use of the questionnaire، which was distributed to a sample of the adult faculty members (95) member، The study used a number of appropriate statistical methods to test the hypotheses. The results indicated that there is a significant impact on the use of ICT faculty to display the teaching content easily. The results also showed that the students’ understanding increased through the use of teaching techniques and increased motivation to learn.